Students’ Engagement in Utilizing Technology For Learning Support - Inderawati, Rita; Sofendi, Sofendi; Purnomo, Mulyadi Eko; Vianty, Machdalena; Suhendi, Didi (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2019)
ABSTRACT: The research is aiming at exploring the utilization of technology at both Faculty of Teacher Training and Education, Sriwijaya University and Faculty of Arts and Education within Deakin Universit.The data was collected through the interview with the lecturers and also the field observation. On this faculty, the BI learning program is organized in two modes: on campus and off campus. Based on the observation and interview, it could be identified that 1) Learning activity: Mode off campus 2) Classroom Management is conducted individually or in group and a virtual meeting with the instructor and or via video conference 3) Devices utilized by the students were hardware and software with certain specification, 4) Application/software utilized was adopted package software, 5) Learning material was developed by the instructors, 6) Supported crew was the IT staff, and 7) Instructur in the learning activity was still required with different role as the learning material developer. Keywords: engagement; technology; learning support